KUALITAS ARANG BRIKET BERDASARKAN PERSENTASE ARANG BATANG KELAPA SAWIT (ELAEIS GUINEENSIS JACQ) DAN ARANG KAYU LABAN (VITEX PUBESCENS VAHL) - Kahariayadi, Aloysius; Setyawati, Dina; haida, Nur; Diba, Farah; Roslinda, Emi (JURNAL HUTAN LESTARI, 2015)
Energy is a major component in all human activities. The main source of energy for humans are natural resources derived from fossil carbon, these are petroleum, coal, and gas . The research aimed to determine the quality of charcoal briquettes based on ration percentage of charcoal oil palm trunks and charcoal Laban wood. This study used a completely randomized design. The percentage of oilpalm trunks charcoal (OTC) and Laban wood charcoal (LWC) as follow: 100% OTC; 20% OTC: 80% LWC; 40% OTC : 60%LWC; 60%OTC : 40% LWC ; 80% : 20% LWC; 100% LWC. Particle size of charcoal was 20 mesh adhesive tapioca flour. The charcoal briquettes size was 30-40 mm heigh with diameter 55 mm and made with hydraulic press with pressure 5 tons. Before testing the quality, charcoal briquettes was dried for 48 hours in oven with temperature 80oC. evaluation the quality of charcoal briquettes based on SNI 01-6235-2000. The average value of moisture content ash content, volatile matter content valve and carbon qualified the SNI 01-6235-2000 standard.Â  The best value was achieved on charcoal briquettes with ratio percentage 40% oil palm trunks charcoal and 60% Laban wood charcoal with average calorific value 6377,67 cal/g. the charcoal briquettes produced can be used as an alternative energy for the society. Keywords: Bioenergy, charcoal briquettes, Laban, oil palm